2015
DOI: 10.1017/s0007114514004401
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and anthropometric measures of obesity in a population sample at high cardiovascular risk from the PREDIMED (PREvención con DIeta MEDiterránea) trial

Abstract: The dietary inflammatory index (DII) is a new tool to assess the inflammatory potential of the diet. In the present study, we aimed to determine the association between the DII and BMI, waist circumference and waist:height ratio (WHtR). We conducted a cross-sectional study of 7236 participants recruited into the PREvención con DIeta MEDiterránea trial. Information from a validated 137-item FFQ was used to calculate energy, food and nutrient intakes. A fourteen-item dietary screener was used to assess adherence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
257
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(297 citation statements)
references
References 61 publications
30
257
10
Order By: Relevance
“…Thus far, the DII has been found to be associated with C-reactive protein [24,25], interleukin-6 [26][27][28], and homocysteine [26]. Additionally, DII has been shown to be associated with glucose intolerance and dyslipidemia components of the metabolic syndrome [25,29], anthropometric measurements in Spain [30], asthma in Australia [28], respiratory conditions in Italy [31], bone mineral density among postmenopausal women in Iran [28], colorectal cancer in two case-control studies in Spain and Italy [32,33], and three cohort studies in the USA [34][35][36], pancreatic [37], prostate [38,39] and esophageal cancers [40,41] and mortality in a cohort among US women [42].…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, the DII has been found to be associated with C-reactive protein [24,25], interleukin-6 [26][27][28], and homocysteine [26]. Additionally, DII has been shown to be associated with glucose intolerance and dyslipidemia components of the metabolic syndrome [25,29], anthropometric measurements in Spain [30], asthma in Australia [28], respiratory conditions in Italy [31], bone mineral density among postmenopausal women in Iran [28], colorectal cancer in two case-control studies in Spain and Italy [32,33], and three cohort studies in the USA [34][35][36], pancreatic [37], prostate [38,39] and esophageal cancers [40,41] and mortality in a cohort among US women [42].…”
Section: Introductionmentioning
confidence: 99%
“…For the updated version, several studies have found associations between DII score and CRP, in adults and seniors [26], and IL-6, tumour necrosis factor-alpha (TNF-α) and another score of combined inflammatory biomarker in postmenopausal women [27]. The DII score has been used in several studies to predict mortality [28,29], survival [30], and diseases, especially cancer [30,31], but also obesity [32], cardiovascular disease [33] and metabolic syndrome [32,34].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the DII has predicted C-reactive protein and interleukin-6 levels using 24-hour dietary recalls (24HR) and 7-day recalls, as well as a food frequency questionnaire (FFQ) [1517]. The DII also has been shown to be associated with the glucose intolerance component of MetSyn, increased odds of asthma, anthropometric measurements, and several cancers [1625]. It also has been shown that shiftworkers from the National Health and Nutrition Examination Study (NHANES) had statistically significant greater DII values (i.e., more pro-inflammatory) compared to day workers [26].…”
Section: Introductionmentioning
confidence: 99%